Looking through a tourist gaze: the Joy of Missing Out (JOMO) and the case of mussels/ Francesc Fusté-Forné and Asif Hussain - Fusté-Forné, Francesc; Hussain, Asif (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The diverse possibilities of online avenues and travel experiences have generally led to the fear of Missing Out (FOMO) sentiment. The FOMO encourages people to spend as much time online as possible searching for exploration opportunities. In contraposition to FOMO, a new movement has recently appeared: the Joy of Missing Out (JOMO) refers to the escape from technology. Applying this concept to tourism, JOMO advocates a 'slow' and 'digital-free' environment. This research looks at food tourism as a crucial example of JOMO that looks at outlying regions from a regenerative tourism point of view. Food tourism is explored through an approach of mussels. Drawing on autoethnography, results show that JOMO is associated with activities that provide "intellectual memories" based on feelings of personal fulfilment. Visitor backgrounds and the accumulation of memorable experiences are the factors that motivate JOMO practices that spread community development in rural tourism.